Anaerobic digestion of high-yielding tropical energy crops for biomethane production: Effects of crop types, locations and plant parts. (August 2018) - Surendra, K.C.; Ogoshi, Richard; Reinhardt-Hanisch, Annett; Oechsner, Hans; Zaleski, Halina M.; Hashimoto, Andrew G.; Khanal, Samir Kumar
Highlights: Anaerobic digestibility of plant parts of two tropical energy crops were examined. Methane yields varied significantly with crop types and plant parts. Specific methane yield correlated negatively with ADF, cellulose and lignin content. Energycane had higher specific and total methane yields than Napier grass. Energycane and Napier grass had total methane yields comparable with maize. Abstract: This study examined the composition and anaerobic digestibility of the different plant parts of two high-yielding tropical energy crops, Energycane and Napier grass, collected across three locations and two seasons. Both biomass composition and biomethane yields varied significantly with crop types, plant parts and harvest seasons. In Energycane, specific methane yield (SMY) (Nm 3 (kg VSadded ) −1 ) was higher from stems (0.232 ± 0.003) than leaves (0.224 ± 0.003), while in Napier grass, SMY was higher from leaves (0.243 ± 0.002) than stems (0.168 ± 0.002). Energycane had higher specific and total (Nm 3  ha −1  year −1 ) methane yields (0.230 ± 0.002 and 8749 ± 494, respectively) than Napier grass (0.192 ± 0.002 and 5575 ± 494, respectively). The SMYs from biomass correlated negatively with acid detergent fiber, cellulose and lignin content in the biomass. Energycane and Napier grass had lower specific but comparable total methane yields (TMYs) with maize. The ecological, economic and environmental merits associated with perennial crops suggest they could outperform maize as a substrate for bioenergy production.